AeU boosts higher education for pre-school educators - New, Sabah Times (New Sabah Times, 2014)
As a role model, teachers need to to stay professional, uphold integrity, and qualify enough to take care of this children, especially the Alpha generation who are highly exposed to elements of technology and materialistics - Prof. Dr. John Arul Philips